STYLISTIC USE OF THE WORD IN THE LITERARY LANGUAGE - Allanazarov, Esbergen Esbosinovich; Esbergenova, Bagdaagul Perdebaevna (SCIENCE and SOCIETY, 2026)
In the article, one of the linguistic unic of our language is devoted to the event of the use of leksem s unic in the artistic language. In the works of X.Dawletnazarov, some details are given concerning the peculiarities of the meaning of the word in use.